POVERTY DEBATES IN THE DEWAN RAKYAT OF THE MALAYSIAN PARLIAMENT - Nazli Aziz (Jurnal Kajian Wilayah, 2017)
This article highlights the nature of parliamentary debates in the Dewan Rakyat (House of Representatives) of the Malaysian Parliament related to the poverty issues in Malaysia. Using qualitative research technique, it focuses on the untold story of poverty in Malaysia that buried in the Dewan Rakyat Hansard. Analysing poverty issues qualitatively, however, can be ambiguous and open to challenge. Despite the success story of poverty eradication in Malaysia, poverty issues have always been debated in almost every parliament proceeding in the Dewan Rakyat. If Malaysia is so successful in eradicating poverty, why the Members of Parliament (MPs) are still debating the issue in the Dewan Rakyat to date? To understand this issue, it uses Hansard records of the Dewan Rakyat (1990-2012) to narrate the multifaceted of poverty issues in both rural and urban consistencies in Malaysia, qualitatively. It reevaluates the previous works on poverty in Malaysia by examining the debates extracted from the Dewan Rakyat Hansard. The aim is to understand whether and to what extent the poverty eradication agendas have benefited communities and spilled over throughout the constituencies in Malaysia.Key words: The Malaysian Parliament, Hansard, Members of Parliament, Dewan Rakyat; poverty eradication AbstrakArtikel ini menyajikan prediksi perdebatan tentang isu kemiskinan di Malaysia yang diungkapkan di Dewan Perwakilan Rakyat, Parlemen Malaysia. Dengan menggunakan teknik penelitian kualitatif, fokus utamanya adalah masih adanya isu kemiskinan di Malaysia yang disematkan dalam Pernyataan Resmi (Hansard) Dewan Perwakilan Rakyat. Namun demikian, menganalisis isu kemiskinan secara kualitatif akan mengundang keabsahan, dan bersifat ambigu serta terbuka terhadap tantangan. Terlepas dari keberhasilan pemberantasan kemiskinan di Malaysia, masalah kemiskinan selalu diperdebatkan hampir di setiap sidang parlemen di Dewan Rakyat. Jika Malaysia berhasil memberantas kemiskinan, mengapa anggota parlemen masih memperdebatkan isu kemiskinan di Dewan Rakyat sampai sekarang? Untuk memahami masalah ini, catatan Pernyataan Resmi, Hansard, Dewan Rakyat (1990-2012) digunakan untuk menggambarkan komposisi isu kemiskinan di daerah perkotaan dan pedesaanndi Malaysia secara kualitatif. Kajian-kajian sebelumnya mengenai kemiskinan di Malaysia dievaluasi kembali dengan meninjau kembali perdebatan yang dikutip dari Pernyataan Resmi, Hansard, Dewan Perwakilan Rakyat. Tujuan utamanya adalah untuk memahami apakah ada dan sejauh mana pengentasan kemiskinan menguntungkan masyarakat dan menyebar ke seluruh wilayah di Malaysia.Kata kunci: Parlemen Malaysia, Hansard (Pernyataan Resmi), Anggota Parlemen, Dewan Perwakilan Rakyat, pengentasan kemiskinan.